Salesforce CRM : The Definitive Admin Handbook - Goodey, Paul; Goodey, Paul (Packt Publishing, 2015)
The book begins by guiding you through setting up users and security settings and then progresses to configuration, data management, and data analytics. Next, you will swiftly move on to how to set up organization-wide features that affect the look and feel of the application. Process automation, and approval mechanisms are then covered, along with the functional areas of Sales Cloud, Service Cloud, Marketing Cloud, and Salesforce Chatter. At the end of the book, we cover Salesforce mobile apps and mobile administration, along with techniques to further enhance the system and improve the return on investment. Prerequisites include Enterprise, Unlimited, Performance, or Developer edition of Salesforce CRM along with the System Administrator permission.